ANALISIS TERHADAP KEPUASAN PELANGGAN DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS PADA PERUSAHAAN LOGISTIK - Marshella Kartika Laraswati; Yesica Novrita Devi; Adianto Adianto (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
Customer satisfaction is a comparison between the performance expected by the customer compared to the actual performance in the field. When the actual performance is higher than the customer's expectations, the customer feels satisfied and vice versa. In the case of logistics companies, customer satisfaction is one of the important factors in creating a good business climate, as an example of the case in logistics companies, which have not been maximal in satisfying customer desires. This study aims to analyze customer satisfaction with services at logistics companies, and determine the attributes attributes that need to be prioritized from the company to achieve customer satisfaction. Attributes of service quality are identified from indicators of customer satisfaction as expressed by Zeithmal et al, namely by TRREASE (Tangibles, Reliability, Responsiveness, Assurance, Empathy). The Importance Performance Analysis method at the suitability level compares the level of interest (expectation) with the level of service performance at the Company. The results of the study using the Importance Performance Analysis method for 25 service attributes of logistics companies obtained an average conformity level of 106%. Based on the Cartesian diagram, there are 10 attributes that have a high importance value for customers, but their performance is still unsatisfactory, each attribute is spread in quadrant A.